2023
DOI: 10.1186/s13062-023-00361-1
|View full text |Cite
|
Sign up to set email alerts
|

ADSC-derived exosomes attenuate myocardial infarction injury by promoting miR-205-mediated cardiac angiogenesis

Abstract: Background Acute myocardial infarction is a major health problem and is the leading cause of death worldwide. Myocardial apoptosis induced by myocardial infarction injury is involved in the pathophysiology of heart failure. Therapeutic stem cell therapy has the potential to be an effective and favorable treatment for ischemic heart disease. Exosomes derived from stem cells have been shown to effectively repair MI injury-induced cardiomyocyte damage. However, the cardioprotective benefits of adi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Recently, mesenchymal stem cells (MSCs) have been taken as the priority in SC-based treatments in regenerative medicine, as they are less immunogenic than other types of SCs (expressing low VHL) and potentiate to escape from the immune system of the recipients [ 17 19 ]. Notably, ADSCs, a common type of MSCs, have been widely investigated because of the edge of a wide range of tissue sources and easy extraction [ 20 ]. Hence, ADSCs were selected in this study to evaluate the ability of BP@SDF1-α to recruit SCs.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, mesenchymal stem cells (MSCs) have been taken as the priority in SC-based treatments in regenerative medicine, as they are less immunogenic than other types of SCs (expressing low VHL) and potentiate to escape from the immune system of the recipients [ 17 19 ]. Notably, ADSCs, a common type of MSCs, have been widely investigated because of the edge of a wide range of tissue sources and easy extraction [ 20 ]. Hence, ADSCs were selected in this study to evaluate the ability of BP@SDF1-α to recruit SCs.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular experiments demonstrated that ADSCs-derived exosomes can promote microvascular ECs proliferation and migration and inhibit cardiomyocytes apoptosis through miRNA-205. This assumption was confirmed via the transfection of ADSC-derived exosomes into MI-induced mice and observing a decrease in cardiac fibrosis, an increase in angiogenesis, and an improvement of cardiac function [ 77 ]. Cardiac fibroblast-derived EVs modulate cardiac remodeling, favoring intercellular communication between cardiomyocytes (CM) and cardiac fibroblasts [ 78 , 79 ].…”
Section: The Epigenetic Role Of Evs In Cardiovascular Damagementioning
confidence: 87%
“…Nowadays, it is known that, in the cardiovascular system, EVs also play important epigenetic-indirect roles in the acute post-myocardial infarction (MI) damage and repair mechanisms inducing myocardial remodeling and cardiac regeneration [ 76 ]. Recently, echocardiographic experiments had shown that exosomes derived from the mesenchymal stem cell of adipose tissue (ADSC) could improve left ventricular ejection fraction, whereas their administration could significantly alleviate MI-induced cardiac fibrosis [ 77 ]. Additionally, ADSC-exosomes treatment has been shown to reduce cardiomyocyte apoptosis, increasing angiogenesis.…”
Section: The Epigenetic Role Of Evs In Cardiovascular Damagementioning
confidence: 99%
“…Additionally, ADSC-Exos containing miRNA-205 promoted angiogenesis. This study provides the primary evidence for the use of ADSC-Exos in the clinical treatment of MI 100 .…”
Section: Applications Of Exosome-loaded Biomaterialsmentioning
confidence: 90%